MENU ENGINEERING SEBAGAI LANGKAH PENETAPAN STRATEGI PEMASARAN PADA RESTORAN SARI LAUT RESTU BALI - MERTA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Engineering Menu Method so called “Unique Method of Menu Analysis and Design” try to answer the probloms faced by restaurant entrepreneur. This method implemeted in “Food Service Operation” in many famous restaurant in the world. Result of the research indicated that: (1) The existence menu at Dewi restu Bali restaurant effect toward achieved food sell target, (2) There are three items of sum menu that analysis is Diod kategory, 5 menu include Plowhorse and 2 menu include Pizzle, and only 5 menu include Star kategory. Based on this result of analysis, so the market strategi have to implemented, are: (a) For Stara kategory through to increase of sell price graduaaly, (b) Plowhorse menu kategory need to see competitor condition, material price and competitor sell price, before to increase the sell price, (c) For Puzzle menu kategory to increase the sell volume only can conducted with increase promotion more selectively, (d) Dog menu kategory will give burden to the the other menu, and (e) The restoran should conduct Engeneering menu periodically.
Keywords: Menu, Strategy, Marketing PENDAHULUAN